(0, 1; 0)-Interpolation on Semi Infinite Interval $(0, ∞)$ (Analysis in Theory and Applications, 2024)
In this paper, we have studied a Pál type (0, 1; 0)-interpolation when Hermite and Lagrange data are prescribed on the zeros of Laguerre polynomial $(L^{(α)}_n)(x),$ $α > −1$ and its derivative $(L^{(α)}_n)' (x)$ respectively. Existence, uniqueness and explicitrepresentation of the interpolatory polynomial $R_n(x)$ has been obtained. A qualitativeestimate for $R_n(x)$ has also been dealt with.
Keywords: Pál type interpolation; Laguerre polynomials; estimate; zeros.